1983
DOI: 10.1128/aac.23.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Conjugational transfer of gentamicin resistance plasmids intra- and interspecifically in Staphylococcus aureus and Staphylococcus epidermidis

Abstract: We have previously reported the transfer of gentamicin resistance (Gmr) plasmids in a mixed culture inter-and intraspecifically between strains of Staphylococcus aureus and Staphylococcus epidermidis isolated at Michael Reese Hospital (Jaffe et al., Antimicrob. Agents Chemother. 21:773-779, 1982). We have now shown that representatives of these plasmids were transferred between apparently nonlysogenic strains of S. aureus either in mixed culture in broth or by filter-mating on agar medium. The mechanism of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 38 publications
5
90
1
1
Order By: Relevance
“…In addition to GTKR, these transformants also acquired ethidium bromide resistance (EbR), a character that has been reported to be encoded on some gentamicin-resistance plasmids (Jaffe et al, 1982;McDonnell et al, 1983). In contrast to these GTKR-EbR transformants that carried pSK 1, GTKR transformants were obtained that lacked pSKl and failed to gain EbR.…”
Section: Plasmid Dna Projiles and Location Of Resistance Determinantsmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition to GTKR, these transformants also acquired ethidium bromide resistance (EbR), a character that has been reported to be encoded on some gentamicin-resistance plasmids (Jaffe et al, 1982;McDonnell et al, 1983). In contrast to these GTKR-EbR transformants that carried pSK 1, GTKR transformants were obtained that lacked pSKl and failed to gain EbR.…”
Section: Plasmid Dna Projiles and Location Of Resistance Determinantsmentioning
confidence: 79%
“…aureus has most frequently been reported to be plasmid-mediated (Soussy et al, 1975;Wood, Carter and Best, 1977;Cohen et al, 1982;Jaffe et al, 1982;McDonnell et al, 1983), although chromosomally-encoded resistance has recently been observed in Australia (Lyon et al, 1983;Townsend, et al, 1983) and elsewhere (Kayser, Homberger and Devaud, 1981;Dowd, Cafferkey and Dougan, 1983). Among the strains isolated at this hospital, aminoglycoside resistance was suspected to be chromosomally encoded in the majority of isolates before 1980.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used for testing sensitivity to other antimicrobial agents, for transformation of plasmid DNA, and for plasmid elimination, were as described previously (Lyon et al, 1983;Gillespie et al, 1984). The transfer of plasmid DNA in mixed culture was performed as described by McDonnell et al (1983).…”
Section: General Proceduresmentioning
confidence: 99%
“…Resistance to the quaternary ammonium compounds benzalkonium chloride (Sigma Chemical Company, St Louis, MO 63 178 USA) and cetyltrimethylammonium bromide (BDH Chemicals Ltd, Poole, England) was tested in L-agar at concentrations of 4 and 2 mg/L, respectively. Mixed culture transfer by the method of McDonnell, Sweeney and Cohen (1983) was used to transfer resistance to strain SK982.…”
Section: Staphylococcus Aureus Strainsmentioning
confidence: 99%